Prolonged exposure to antibiotics and its associations in extremely preterm neonates - the Western Australian experience. (November 2013) - Shah, P.; Nathan, E.; Doherty, D.; Patole, S.
Abstract Background: Prolonged exposure to antibiotics (PEA) is associated with increased risk of necrotising enterocolitis (NEC), late onset sepsis (LOS) and death in preterm neonates. Aim: To evaluate PEA (≥4 d) for suspected (blood culture negative) sepsis and its association with NEC, LOS and death in extremely preterm (EP: Gestation <28 weeks) neonates. Methods: Data on demographic characteristics, antibiotic exposure for early onset sepsis (EOS) or LOS and outcomes to discharge/death were collected for 216 EP neonates admitted between 1/1/2009 and 31/12/2010. Results: All 216 neonates received antibiotics for suspected EOS; 120/216 (56%) had PEA. 137/216 who survived first 72 h of life, had suspected LOS [range 1–8 episodes], treated with antibiotics for median (IQR) duration of 8 (5–14) days. 89/216 had proven (blood culture positive) LOS [range 1–3 episodes], treated with antibiotics for median (IQR) duration of 10 (7–18) days. The incidence of and death due to ≥Stage II NEC was 17/216 (7.8%) and 5/17 (29.4%) respectively. PEA for suspected EOS was associated with proven LOS (OR: 2.1, 95% CI: 1.2–3.7, p = 0.013) after adjusting for gestation and IUGR, but not with NEC/death. Conclusion: PEA for ≥4 d for suspected EOS was associated with increased odds for proven LOS.